دور المراجعة الداخلية - طرشون, علي (My University, 2020)
This study aims at the concept of the role of internal audit in the study and analysis of financial statements so that the presence of a strong internal audit in the institution would enhance the consideration that the financial statements are tables that summarize the activity of the institution during the accounting cycle, and is studied with decision-makers by comparing it with the previous financial statements This is to extract appropriate indicators and indications that help them understand the financial position of the institution and its financial position.
دراسة وتحليل القوائم المالية دراسة حالة مؤسسة محاجر الغرب
Keywords: المراحعة الداخلية, القوائم المالية, الىظام المحاسبي المالي, التحليل المالي.